2009
DOI: 10.1002/bjs.6753
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of a randomized clinical trial of hospitalversustelephone follow-up after treatment for breast cancer

Abstract: Telephone follow-up for breast cancer may reduce the burden on busy hospital clinics but will not necessarily lead to cost or salary savings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 19 publications
3
51
0
1
Order By: Relevance
“…Six studies [16,26,33,42,44,51] examined outcomes and costs of a variety of diagnostic tools (e.g., positron-emission tomography vs computed tomography) while four studies [14,23,38,41] related to cervical cancer compared human papilloma virus (HPV) test versus cytology as potential instruments to detect new lesions. Four studies [25,30,34,49] compared costs and health gains arising from a surveillance program versus a 'do nothing' strategy; 11 studies examined traditional hospital-based followup programs in comparison with programs led by other healthcare professionals (i.e., in eight cases [20,31,35,36,43,46,48,52] the nurse and in three [17,19,28] the family physician). One study [15] compared a mobile-app follow-up versus traditional in-person consultations and another one [24] described two programs with (and without) an educational session.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Six studies [16,26,33,42,44,51] examined outcomes and costs of a variety of diagnostic tools (e.g., positron-emission tomography vs computed tomography) while four studies [14,23,38,41] related to cervical cancer compared human papilloma virus (HPV) test versus cytology as potential instruments to detect new lesions. Four studies [25,30,34,49] compared costs and health gains arising from a surveillance program versus a 'do nothing' strategy; 11 studies examined traditional hospital-based followup programs in comparison with programs led by other healthcare professionals (i.e., in eight cases [20,31,35,36,43,46,48,52] the nurse and in three [17,19,28] the family physician). One study [15] compared a mobile-app follow-up versus traditional in-person consultations and another one [24] described two programs with (and without) an educational session.…”
Section: Resultsmentioning
confidence: 99%
“…A societal perspective estimating broader costs to society (i.e., out-of-pocket costs, informal care and productivity losses) irrespective of the payer was adopted by seven studies. The remaining three articles [20,24,42] presented study results according to both healthcare and societal perspectives.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…reported that nurse-led telephone follow-up for breast cancer patients represented savings for patients in terms of time and money but was more costly to the UK's National Health Service (NHS) as telephone calls were longer than hospital appointments and were made by senior nurses [56]. However, Kimman et al (2011) carried out an economic evaluation of four follow-up strategies after curative treatment for breast cancer in the Netherlands and concluded that nurse-led telephone follow-up was a cost effective alternative to hospital follow-up for breast cancer patients during their first year after treatment Revised submission position paper 31.12.16…”
Section: Economic Evaluation Of Oncology Follow-upmentioning
confidence: 99%